Left ventricular outflow tract shape after aortic valve replacement with St. Jude Trifecta prosthesis. Issue 3 (22nd December 2017) - Barletta, Giuseppe; Venditti, Francesco; Stefano, Pierluigi; Del Bene, Riccarda; Di Mario, Carlo
Abstract : Background: Aortic prosthesis area (EOA) is computed by continuity equation from left ventricular (LV) stroke volume (SV) derived from LV outflow tract diameter (LVOTD ) or, when unmeasurable, from LV volumes (SVV ). There is evidence to suggest LVOT ellipticity and recommend 3D LVOT area (LVOTCSA ) adoption in aortic stenosis. We sought to evaluate if the same concept applies to supra‐annular aortic prosthesis comparing SV and EOA derived from LVOTD (EOAD ) and from LVOTCSA (EOACSA ). EOA computed from SVV (EAOV ) accuracy was evaluated in this setting. Patient‐prosthesis mismatch (PPM) was compared among different EOA computations. Methods: A consecutive series of 202 patients (aged 81 ± 4 years, 43% males) underwent St.Jude Trifecta aortic valve replacement (AVR) and were followed up with echocardiography at one‐year (335 ± 31 days). All measurements followed the EACVI or ASE guidelines, 3D X‐plane modality was used to compute SVv and measure LVOTCSA ; SV was calculated from LVOTD (SVD ) and LVOTCSA (SVCSA ). PPM was indexed EOA <0.65 cm²/m². Results: LVOT showed a significant ellipticity index (1.17 ± .27), independent of prosthesis size. EOAD (1.70 ± 0.55 cm²) was less than EOACSA (1.95 ± 0.62 cm²) ( P  < .0001). SVV was significantly lower than SVD and SVCSA . Bland–Altman analysis showed a significant correlation between SVV and SVD or SVCSA although with large bias and imprecision. The correlations improved reducing bias and imprecision when LVOT time–velocity integral was <20 cm. PPM incidence was higher in EOAV (15.6%) compared to EOAD ( P  = .04) or EOACSA ( P  < .001). Conclusions: In supra‐annular AVR, LVOT retains its elliptical shape and LVOTCSA yielded larger prosthesis EOA with lower PPM incidence. PPM may be overestimated by EOAV .